2013
DOI: 10.1139/cgj-2012-0390
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modeling of progressive failure and its implications for spreads in sensitive clays

Abstract: Spreads are a type of large landslide occurring in sensitive clays. Stability analyses using the limit equilibrium method give factors of safety that are too large and are therefore not applicable to this type of landslide. The progressive failure mechanism is believed to explain the initiation and propagation of the failure surface and the dislocation of the soil mass in horsts and grabens, typical of spreads. A numerical method is presented to identify the parameters influencing progressive failure and to va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
74
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(80 citation statements)
references
References 20 publications
6
74
0
Order By: Relevance
“…Quinn et al (2011), using fracture mechanism developed by Palmer and Rice (1973), and Locat et al (2011Locat et al ( , 2013, extending progressive failure mechanism described by Bernander (2000Bernander ( , 2008Bernander ( , 2011, studied the mechanisms forming spreads in sensitive clays. It was suggested that these ground movements involve two processes: (i) the propagation of a quasi-horizontal failure surface by progressive failure; and (ii) the dislocation of the overlying soil mass in horsts and grabens.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Quinn et al (2011), using fracture mechanism developed by Palmer and Rice (1973), and Locat et al (2011Locat et al ( , 2013, extending progressive failure mechanism described by Bernander (2000Bernander ( , 2008Bernander ( , 2011, studied the mechanisms forming spreads in sensitive clays. It was suggested that these ground movements involve two processes: (i) the propagation of a quasi-horizontal failure surface by progressive failure; and (ii) the dislocation of the overlying soil mass in horsts and grabens.…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that these ground movements involve two processes: (i) the propagation of a quasi-horizontal failure surface by progressive failure; and (ii) the dislocation of the overlying soil mass in horsts and grabens. Locat et al (2011Locat et al ( , 2013 describe how progressive failure can be initiated near the toe of a slope and can propagate into the deposit, generating active failure of the soil mass, which results in horsts and grabens, typical of spreads. With this mechanism, the failure propagates in undrained conditions in a soil exhibiting a strain-softening behaviour, which is typical of eastern Canadian sensitive clays (Leroueil et al 1983).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6), at least 0.5 km from valley slope breaks. They must then have undergone progressive failure similar to those described by Locat et al (2013). While the points of initiation contrast with the valley slope initiation at Mink Creek, similar zones of spreading and flowing are recognizable from LiDAR-based morphologies.…”
Section: Lidar Evidence Of Landslidesmentioning
confidence: 79%
“…Composite landslides (Cruden and Varnes, 1996) may occur that display both spreading and flowing behaviour (Geertsema et al, 2006b). The landslides may be triggered by bank erosion and move retrogressively, or by external loads and display progressive movement (Locat et al, 2013. Whether these sensitive clay landslides initiate at a break in the valley slope, or are triggered some distance behind the break in slope, the scarps usually migrate landward.…”
Section: Introductionmentioning
confidence: 99%